Evaluación del impacto financiero y las estrategias administrativas en la implementación de las NIIF para pymes en el sector veterinarias de la ciudad de Villavicencio. Estudio del caso Empresa la Vaca y el Toro (2020)
This research project as a degree option seeks to determine and analyze the impact on the financial statements of the implementation of the Niif for pymes in the Veterinary sector in the city of Villavicencio, as well as the administrative and managerial strategies used to face said financial impact. Determined the development of this project through a case study of mixed nature. The center of this project is based on analyzing the most important variations and impacts in the accounting accounts of the statement of financial position and statement of comprehensive income when implementing the Niif Para SMEs in companies of the veterinary sector located in the city of Villavicencio, Meta. This analysis will be carried out in the most important areas. Besides also determining the strategies and methods used by this management or administration to face said implementation. The development of this research will be carried out through a case study methodology, where information will be collected from instruments such as the critical interpretation of internal financial documentation, interviews and conversations with the defined management group